Medium-term population development and responses to habitat conditions of a beetle, Osmoderma eremita, inhabiting hollow trees - Tranberg, Olle (SLU/Southern Swedish Forest Research Centre, 2016)
Old oaks play an important role in the southern Swedish landscape by maintaining available habitats for many saproxylic species, several of which today are on the international Red List of threatened species. Old oaks can develop important habitats, such as hollows with wood mould, which is the habitat for the European hermit beetle (Osmoderma eremita). Habitat fragmentation as well as habitat qualities are important features that affect population sizes of O. eremita, although, most previous studies have only examined this relationship in a short-term perspective. This study investigated the medium-term population development of O. eremita, colonization and extinction rates and furthermore population trends related to tree variables that previously have affected beetles associated with hollow trees. The study combined data, covering a period of 20 years from a well-studied area with O. eremita in Östergötland, southern Sweden, concerning habitat variables and captures of O. eremita, including several previous publications, unpublished data, and new measurements in 2015. Population development of O. eremita has not previously been investigated to the same extent as in this study. Results demonstrate that hollow trees can be usable as habitat for long time; the study indicates that 9.7% of the examined trees were usable as habitat ≥20 years. The results revealed that local populations of O. eremita have developed both negatively and positively during the study period, leaving the overall population trend unchanged. In a medium-term perspective habitat colonization and extinction rate of O. eremita revealed corresponding rates (0.80% respectively 0.64%), indicating that colonization is compensating for extinction. Several habitat variables alter responses on population development. Tree age, sun exposure of entrance hole and canopy closure revealed significant positive correlations to population development, while tree circumference indicated a significant negative correlation. Death of inhabited hollow trees has a negative effect on population development. The results also revealed that the observed annual tree mortality rate was moderate (0.90%) and comparable to previous studies.